2010
DOI: 10.1021/bi101448t
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Physiological Characterization of a BLUF Protein−EAL Protein Complex Involved in Blue Light-Dependent Degradation of Cyclic Diguanylate in the Purple Bacterium Rhodopseudomonas palustris

Abstract: Organisms adapt their physiologies in response to the quality and quantity of environmental light. Members of a recently identified photoreceptor protein family, BLUF domain proteins, use a flavin chromophore to sense blue light. Herein, we report that PapB, which contains a BLUF domain, controls the biofilm formation of the purple photosynthetic bacterium Rhodopseudomonas palustris. Purified PapB undergoes a typical BLUF-type photocycle, and light-excited PapB enhances the phosphodiesterase activity of the EA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
61
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 63 publications
(135 reference statements)
3
61
0
Order By: Relevance
“…How the extracellular environment impacts the synthesis and degradation of intracellular c-di-GMP is poorly understood. It has been proposed that extracellular stimuli, such as oxygen, light, amino acids, and QS autoinducers, regulate intracellular c-di-GMP by altering the activity of DGCs and PDEs (16)(17)(18)(19)(20)(21)(22)(23)(24). Also, many DGCs and PDEs have domains predicted to be involved in sensing extracellular ligands (54).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…How the extracellular environment impacts the synthesis and degradation of intracellular c-di-GMP is poorly understood. It has been proposed that extracellular stimuli, such as oxygen, light, amino acids, and QS autoinducers, regulate intracellular c-di-GMP by altering the activity of DGCs and PDEs (16)(17)(18)(19)(20)(21)(22)(23)(24). Also, many DGCs and PDEs have domains predicted to be involved in sensing extracellular ligands (54).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that extracellular factors regulate DGCs and PDEs, altering the intracellular concentration of c-di-GMP to adapt to changing environments. Indeed, some environmental signals, such as light, oxygen, amino acids, quorum-sensing autoinducers, and norspermidine, have been shown to alter intracellular c-di-GMP in various bacteria (16)(17)(18)(19)(20)(21)(22)(23)(24). However, the vast majority of the regulatory inputs that control DGCs and PDEs remain undetermined.…”
mentioning
confidence: 99%
“…As discussed above (see "Regulation by Sensory Domains"), many enzymes involved in c-di-GMP signaling contain sensory domains and respond to specific signals. Some enzymes respond to environmental signals by interacting with sensor proteins (136,368). At present, a relatively limited number of signals affecting activities of the c-di-GMP-metabolizing proteins have been investigated experimentally.…”
Section: Gmp Signaling Pathwaysmentioning
confidence: 99%
“…One hypothesis is that each DGC or PDE senses and responds to a specific environmental signal by altering c-di-GMP synthesis or degradation activity in the C-terminal domain. While a few environmental cues, including light, oxygen, zinc, arginine, quorum sensing (QS) autoinducers, and norspermidine, have been shown to directly regulate DGCs or PDEs in various bacteria (14,(16)(17)(18)(19)(20)(21)(22)(23)(24), the environmental signals recognized by the vast majority of DGCs and PDEs remain unidentified.…”
mentioning
confidence: 99%